Prebiotically Plausible Autocatalytic Peptide Amyloids. Issue 3 (20th December 2021) - Rout, Saroj K.; Rhyner, David; Riek, Roland; Greenwald, Jason
Abstract: The prebiotic emergence of molecules capable both of self‐replication and of storing information was a defining event at the dawn of life. Still, no plausible prebiotic self‐replication of biologically relevant molecules has been demonstrated. Building upon the known templating nature of amyloids, we present two systems in which the products of a peptide‐bond‐forming reaction act as self‐replicators to enhance the yield and stereoselectivity of their formation. This first report of an amino acid condensation that can undergo autocatalysis further supports the potential role of amyloids in prebiotic molecular evolution as an environment‐responsive and information‐coding system capable of self‐replication. Abstract : The plus side of amyloids ? Peptide amyloids have an inherent templating ability that underlies the infectivity and progression of prion and other neurodegenerative diseases as well as guiding the synthesis of melanin. Such amyloid‐based templating has been shown to support the sequence‐selective, regioselective and stereoselective addition of amino acids to a complementary peptide chain. Here we report that the templating nature of amyloids also supports the autocatalytic self‐replication of peptides. The relevance to a prebiotic role for amyloids is discussed.